2017
DOI: 10.1074/jbc.m117.802504
|View full text |Cite
|
Sign up to set email alerts
|

The glucose sensor Snf1 and the transcription factors Msn2 and Msn4 regulate transcription of the vacuolar iron importer gene CCC1 and iron resistance in yeast

Abstract: The budding yeast stores iron in the vacuole, which is a major resistance mechanism against iron toxicity. One key protein involved in vacuolar iron storage is the iron importer Ccc1, which facilitates iron entry into the vacuole. Transcription of the gene is largely regulated by the binding of iron-sulfur clusters to the activator domain of the transcriptional activator Yap5. Additional evidence, however, suggests that Yap5-independent transcriptional activation of also contributes to iron resistance. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…We demonstrated that the iron importer and calcium transports, Ct‐1 and Ct‐2, were important in MS formation (Wang and Yin, unpublished data). In addition to similar transcriptional mechanisms by Msn2/4 for regulating ccc1 in yeast (Li et al ., 2017), we found multiple transcriptional mechanisms for regulating genes for iron and calcium cation transport and storage by MrMsn2 during MS development (Fig. 5).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We demonstrated that the iron importer and calcium transports, Ct‐1 and Ct‐2, were important in MS formation (Wang and Yin, unpublished data). In addition to similar transcriptional mechanisms by Msn2/4 for regulating ccc1 in yeast (Li et al ., 2017), we found multiple transcriptional mechanisms for regulating genes for iron and calcium cation transport and storage by MrMsn2 during MS development (Fig. 5).…”
Section: Discussionmentioning
confidence: 82%
“…They are similar to ScMsn2/4 of Saccharomyces cerevisiae (Schmitt and Mcentee, 1996) and have been characterized in Aspergillus parasiticus , A. flavus , Beauveria bassiana , Magnaporthe oryzae , Metarhizium robertsii and Verticillium dahliae (Chang et al ., 2011; Liu et al ., 2013; Zhang et al ., 2014; Tian et al ., 2017). Under abiotic and biotic stresses, Msn2/4 is phosphorylated for translocation from the cytoplasm to the nucleus, where it drives the transcription of stress‐induced genes (Hansen et al ., 2015; Yi and Huh, 2015; Li et al ., 2017). The underlying mechanism of the regulation of Msn2/4 activity by protein kinase A (PKA), the rapamycin signalling pathway, the Snf1 protein kinase pathway and the high‐osmolarity glycerol (HOG) pathway have been identified (Liu et al ., 2013; Zhang et al ., 2014; Li et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of Ccc1 results in increased sensitivity to iron toxicity and cell death. In yeast, Ccc1 levels are tightly regulated by transcription (Li et al 2008, 2011, 2012, 2017; Rietzschel et al 2015) and by mRNA degradation (Puig et al 2005, 2008). In this review, we will focus on the transcriptional regulation of iron sensing in S. cerevisiae and how Ccc1 levels are controlled by the high iron-sensing transcription factor Yap5 and Snf1 kinase signaling to the stress transcription factors Msn2 and Msn4.…”
Section: Introductionmentioning
confidence: 99%
“…Yeast have developed several stress-activated signaling networks to deal with deprivation or excess nutrients conditions (Ho and Gasch 2015; Nishida-Aoki et al 2015; Yadav et al 2016). Recently, a role for the low-glucose sensor Snf1 kinase complex [for review see (Conrad et al 2014)] in regulating CCC1 transcription has been identified (Li et al 2017). Under iron-replete conditions, the absence of Yap5 and Snf1 has an additive effect on CCC1 transcription with the concomitant decrease in Ccc1 protein levels, increased sensitivity to iron toxicity and poor growth.…”
Section: Introductionmentioning
confidence: 99%